2021
DOI: 10.1007/s00604-021-04838-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical immunosensor development based on core-shell high-crystalline graphitic carbon nitride@carbon dots and Cd0.5Zn0.5S/d-Ti3C2Tx MXene composite for heart-type fatty acid–binding protein detection

Abstract: Acute myocardial infarction (AMI) is a significant health problem owing to its high mortality rate. Heart-type fatty acid-binding protein (h-FABP) is an important biomarker in the diagnosis of AMI. In this work, an electrochemical h-FABP immunosensor was developed based on Cd 0.5 Zn 0.5 S/d-Ti 3 C 2 T x MXene (MXene: Transition metal carbide or nitride) composite as signal amplificator and core-shell high-crystalline graphitic carbon nitride@carbon dots (hc-g-C 3 N 4 @CDs) as electrochemical sensor platform. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…CDs-based antibody sensors have also shown evidence in monitoring cardiovascular diseases like acute myocardial infarction (AMI). Very recently, Karaman and co-workers reported an electrochemical immunosensor for detecting heart-type fatty acid-binding protein (h-FABP), which is significant for the early diagnosis of AMI [227]. Herein, coreshell high-crystalline graphitic carbon nitride decorated carbon dots (hc-g-C 3 N 4 @CDs) and Cd 0.5 Zn 0.5 S/d-Ti 3 C 2 Tx MXene nanocomposite (MXene: Transition metal nitride or carbide) were employed as electrode modifiers for signal amplification.…”
Section: Applications Of Cds In Electrochemical Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…CDs-based antibody sensors have also shown evidence in monitoring cardiovascular diseases like acute myocardial infarction (AMI). Very recently, Karaman and co-workers reported an electrochemical immunosensor for detecting heart-type fatty acid-binding protein (h-FABP), which is significant for the early diagnosis of AMI [227]. Herein, coreshell high-crystalline graphitic carbon nitride decorated carbon dots (hc-g-C 3 N 4 @CDs) and Cd 0.5 Zn 0.5 S/d-Ti 3 C 2 Tx MXene nanocomposite (MXene: Transition metal nitride or carbide) were employed as electrode modifiers for signal amplification.…”
Section: Applications Of Cds In Electrochemical Sensorsmentioning
confidence: 99%
“…Subsequently, the primary antibodies were bio-immobilized onto the surface of hc-g-C 3 N 4 @CDs. Thereafter, Cd 0.5 Zn 0.5 S/d-Ti 3 C 2 Tx MXene nanocomposites were fused with secondary antibodies via strong electrostatic and π-π interactions [227]. The characterization of as-constructed antibody sensors was achieved using EIS, cyclic voltammetry (CV), XPS, FTIR, XRD, SEM, and TEM.…”
Section: Applications Of Cds In Electrochemical Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon nanomaterials play an important role in bioelectrocatalytic reactions due to their high specific surface area and their better biocompatibility (Naderi Asrami et al, 2020;Karaman et al, 2021;Karimi-Maleh et al, 2021b). Their large specific surface area and high surface reactivity lead to enhanced adsorption capacity of the materials, increased active sites on the surface, and improved catalytic efficiency.…”
Section: Carbon Materials Based Electrochemical Biosensorsmentioning
confidence: 99%
“…This led to the use of tumor markers Li et al (2020a), Duan et al (2021), Li et al (2021), Wang et al (2021), which are chemical-based substances that reflect the presence of tumors. They are not found in normal adult tissues but only in embryonic tissues Karimi-Maleh et al (2021c), Karaman (2021), Karaman et al (2021), or are present in tumor tissues at levels that greatly exceed those found in normal tissues (Li et al, 2020b;Vajhadin et al, 2020). Their presence or quantitative changes can reveal the nature of tumors, lend to the understanding of tumor histogenesis, cell differentiation and cell function, which can provide assistance in tumor diagnosis, classification and treatment guidance.…”
Section: Introductionmentioning
confidence: 99%